Circulative Nonpropagative Aphid Transmission of Nanoviruses: an Oversimplified View - Sicard, Anne (J Virol, 2015)
Plant virus species of the family Nanoviridae have segmented genomes with the highest known number of segments encapsidated individually. They thus likely represent the most extreme case of the so-called multipartite, or multicomponent, viruses. All species of the family are believed to be transmitted in a circulative nonpropagative manner by aphid vectors, meaning that the virus simply crosses cellular barriers within the aphid body, from the gut to the salivary glands, without replicating or even expressing any of its genes. However, this assumption is largely based on analogy with the transmission of other plant viruses, such as geminiviruses or luteoviruses, and the details of the molecular and cellular interactions between aphids and nanoviruses are poorly investigated. When comparing the relative frequencies of the eight genome segments in populations of the species Faba bean necrotic stunt virus (FBNSV) (genus Nanovirus) within host plants and within aphid vectors fed on these plants, we unexpectedly found evidence of reproducible changes in the frequencies of some specific segments. We further show that these changes occur within the gut during early stages of the virus cycle in the aphid and not later, when the virus is translocated into the salivary glands. This peculiar observation, which was similarly confirmed in three aphid vector species, Acyrthosiphon pisum, Aphis craccivora, and Myzus persicae, calls for revisiting of the mechanisms of nanovirus transmission. It reveals an unexpected intimate interaction that may not fit the canonical circulative nonpropagative transmission. IMPORTANCE A specific mode of interaction between viruses and arthropod vectors has been extensively described in plant viruses in the three families Luteoviridae, Geminiviridae, and Nanoviridae, but never in arboviruses of animals. This so-called circulative nonpropagative transmission contrasts with the classical biological transmission of animal arboviruses in that the corresponding viruses are thought to cross the vector cellular barriers, from the gut lumen to the hemolymph and to the salivary glands, without expressing any of their genes and without replicating. By monitoring the genetic composition of viral populations during the life cycle of Faba bean necrotic stunt virus (FBNSV) (genus Nanovirus), we demonstrate reproducible genetic changes during the transit of the virus within the body of the aphid vector. These changes do not fit the view that viruses simply traverse the bodies of their arthropod vectors and suggest more intimate interactions, calling into question the current understanding of circulative nonpropagative transmission.